SERUM LIPID LEVELS IN PATIENTS WITH LICHEN PLANUS - Alnasser, Remi Sameer; Souliman, Hamid; Khaddam, Jamal (Journal of medical and pharmaceutical sciences, 2021)
Background: Lichen planus (LP) is a chronic inflammatory disease, involving the skin, mucous membranes, hair, and nails. Cardiovascular risk factors have been assessed with some chronic inflammatory skin diseases such as alopecia and psoriasis. Recently, some studies found that lichen planus (LP) was associated with dyslipidemia. So we did this study to find this association in our patients. Objective: To evaluate lipid levels in patients with L.P and compare it with controls. Materials and Methods: This case- control study included 160 participators (80 with L.P. and 80 controls) admitted to dermatology clinic at Tishreen University Hospital, Lattakia, Syria, from 2020- 2021. Results: Cholesterol, triglyceride and Low- density lipoprotein (LDL) levels in patients were significantly higher than the control group; it was only regarding high- density lipoprotein (HDL) levels that no significant difference was observed between the two groups. Triglyceride levels were significantly higher and HDL levels were lower in patients with diffused disease. There was a recognizable correlation between elevated levels of LDL and cholesterol with disease duration. Conclusion: In this study, a disrupted lipid profile was observed in LP patients, which can be associated with disease severity. This study proposes measuring lipid serum levels prior to commencing the treatment in all known cases of lichen planus, so as to preclude cardiovascular diseases if there is a problem with the lipid profile.